Associations between single nucleotide polymorphisms in the calcium sensing receptor and chronic kidney disease-mineral and bone disorder in cats. (May 2018) - Geddes, R.F.; Jepson, R.E.; Forcada, Y.; Elliott, J.; Syme, H.M.
Highlights: Twelve polymorphisms have now been identified in the feline calcium sensing receptor. One polymorphism was associated with parathyroid hormone concentration at diagnosis of CKD in non-pedigree cats. No associations yet identified between identified polymorphisms and ionised calcium or phosphate in non-pedigree cats. Abstract: Feline chronic kidney disease (CKD) is associated with high variability in severity of CKD-mineral and bone disorder (CKD-MBD). The calcium sensing receptor (CaSR) regulates circulating parathyroid hormone (PTH) and calcium concentrations. Single nucleotide polymorphisms (SNPs) in the CaSR are associated with severity of secondary renal hyperparathyroidism and total calcium concentrations in human patients receiving haemodialysis. The objective of this study was to explore associations between polymorphisms in the feline CaSR (fCaSR) and biochemical changes observed in CKD-MBD. Client owned cats (≥9 years) were retrospectively included. SNP discovery was performed in 20 cats with azotaemic CKD and normal or dysregulated calcium concentrations. Non-pedigree cats ( n  = 192) (125 with azotaemic CKD and 66 healthy), Persians ( n  = 40) and Burmese ( n  = 25) were genotyped for all identified SNPs using KASP. Biochemical parameters from the date of CKD diagnosis or from first visit to the clinic (healthy cats) were used. Associations between genotype and ionized calcium, total calcium, phosphate, PTH and FGF-23 were performed for non-pedigree cats using logistic regression. Sequence alignment against the fCaSR sequence revealed eight novel exonic SNPs. KASP genotyping had high accuracy (99.6%) and a low failure rate (<6%) for all SNPs. Allele frequencies varied between breeds. In non-pedigree cats, one synonymous SNP CaSR:c.1269G > A was associated with logPTH concentration (adjusted for plasma creatinine concentration), with a recessive model having the best fit (G/G vs A/A-G/A, P  = 0.031). Genetic variation in the fCaSR is unlikely to explain the majority of the variability in presence and severity of CKD-MBD in cats.